Searching for Sky - Cantor, Jillian (Scholastic, 2014)
On her sixteenth birthday, Sky and River, the boy with whom she has shared Island since she was a toddler, are "rescued" and taken to California, where Sky is separated from River, forced to live with a grandmother she has just met, and learn new rules for survival.